Biosourced polymer electrolytes based on cellulose derivative for application in electrochemical cell / Mohd Saiful Asmal Abdul Rani - Mohd Saiful Asmal, Abdul Rani (2018)
The aim of this study was to investigate the characteristics of a new type environmental friendly biopolymer electrolyte as potential applications in electrochemical cell. A cellulose derivative, carboxymethyl cellulose, CMC was synthesized by the reaction of cellulose from kenaf bast fiber with monochloroacetic acid. A series of solid biopolymer electrolytes comprised of the synthesized CMC as the host for acetate based salts; (ammonium, sodium, magnesium, zinc) and ionic liquid 1-butyl-3-methylimidazolium chloride which played role as ionic dopants and plasticizer, respectively. All biopolymer electrolyte films were successfully prepared via solution casting technique. The biopolymer electrolyte films obtained were transparent and flexible. The properties of the synthesized CMC depend on the degree of substitution of the hydroxyl group, which took part in the substitution reaction in the cellulose, respectively, as well as the purity, molecular weight and crystallinity was determined using acid-wash method. The degree of substitution value obtained was higher than that of commercial CMCs available in market. This means that the CMC had a higher number of oxygens, thus providing more active sites for coordination with the cations of the doping salt, resulting in a higher conductivity value. The prepared films were characterized using various characterization techniques such as Fourier transform infrared spectroscopy, dynamic mechanical analysis, thermogravimetric analysis, impedance spectroscopy, linear sweep voltammetry and transference number measurement in order to investigate the structural, thermal, electrical and electrochemical properties. The interactions between the biopolymer host with the ionic dopant and plasticizer were indicated by Fourier transform infrared spectroscopy. Impedance spectroscopy was conducted to obtain their ionic conductivities. The influence of sodium acetate into the biopolymer system showed the highest ionic conductivity compared to other acetate based salts, which increased up to optimum value of 2.83 × 10-3 S cm-1 at room temperature for sample containing 30 wt% of sodium acetate. The conductivity was higher compared to that obtained for polymer electrolytes developed using commercial CMC. This was due to high DS value which provided more ion coordinate sites. The best conductivity achieved was 4.54 × 10-3 S cm-1 for the sample integrated with 30 wt% ionic liquid. The conductivity was enhanced upon addition of ionic liquid. All biopolymer electrolyte films were amorphous and have low glass transition temperature which facilitated segmental motion of the host polymer. The temperature dependence of the ionic conductivity of the biopolymer electrolyte systems obeyed the Arrhenius relation. Furthermore, all conducting biopolymer electrolytes showed an electrochemical stability more than 2 V, whereas the transference number measurement revealed that ions predominated the conduction of electrolytes. Electrochemical cell was prepared using configuration Na/ CMC-NaCH3COO-30 wt% [Bmim]Cl/ I2+ C+ electrolyte and the discharge characteristics was studied. The results revealed that the biopolymer electrolytes from kenaf fiber have potential for application in electrochemical devices.